Why is the mastery of key competencies in mathematics for Indonesian students low? : Re-analysis of PISA 2012 - Kartianom Kartianom; Rika Damayanti; Musdalifah Musdalifah (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to determine the level of mastery of the key competency attributes of Indonesian students in mathematics. This study was approached quantitatively by adopting approach retrofitting (posthoc analysis). The data sources for this study were Indonesian students aged 15 years who took part in PISA 2012, as many as 5,622 students. The data of this research are ex post facto data obtained by documentation technique, as for what will be documented in the form of response data from Indonesian students based on the results of PISA 2012 and PISA 2012 instruments (item release PISA2012). The data analysis technique used is descriptive statistics using the DINA package R application. The results of this study indicate that Indonesian students are low in mastering the key competency attributes of mathematics related to mathematical operation (MO) and data analysis (DA); high in the mastery of key mathematical competency attributes related to mathematical abstraction (MA), logical reasoning (LR), mathematical modeling (MM), and intuitive imagination (II).